Observation of momentum-dependent charge density wave gap in a layered antiferromagnet $${Gd}{Te}_{3}$$ Gd Te 3 - Sabin Regmi; Iftakhar Bin Elius; Anup Pradhan Sakhya; Dylan Jeff; Milo Sprague; Mazharul Islam Mondal; Damani Jarrett; Nathan Valadez; Alexis Agosto; Tetiana Romanova; Jiun-Haw Chu; Saiful I. Khondaker; et al. (Scientific Reports, 2023)
Abstract Charge density wave (CDW) ordering has been an important topic of study for a long time owing to its connection with other exotic phases such as superconductivity and magnetism. The $$RTe_{3}$$ R Te 3 (R = rare-earth elements) family of materials provides a fertile ground to study the dynamics of CDW in van der Waals layered materials, and the presence of magnetism in these materials allows to explore the interplay among CDW and long range magnetic ordering. Here, we have carried out a high-resolution angle-resolved photoemission spectroscopy (ARPES) study of a CDW material $${Gd}{Te}_{3}$$ Gd Te 3 , which is antiferromagnetic below $$\sim 12~K$$ ∼ 12 K , along with thermodynamic, electrical transport, magnetic, and Raman measurements. Our ARPES data show a two-fold symmetric Fermi surface with both gapped and ungapped regions indicative of the partial nesting. The gap is momentum dependent, maximum along $${\overline{Γ }}-\mathrm{\overline{Z}}$$ Γ ¯ - Z ¯ and gradually decreases going towards $${\overline{Γ }}-\mathrm{\overline{X}}$$ Γ ¯ - X ¯ . Our study provides a platform to study the dynamics of CDW and its interaction with other physical orders in two- and three-dimensions.